Hair follicle stem cell progeny heal blisters while pausing skin development. (4th June 2021) - Fujimura, Yu; Watanabe, Mika; Ohno, Kota; Kobayashi, Yasuaki; Takashima, Shota; Nakamura, Hideki; Kosumi, Hideyuki; Wang, Yunan; Mai, Yosuke; Lauria, Andrea; Proserpio, Valentina; Ujiie, Hideyuki; et al.
Abstract: Injury in adult tissue generally reactivates developmental programs to foster regeneration, but it is not known whether this paradigm applies to growing tissue. Here, by employing blisters, we show that epidermal wounds heal at the expense of skin development. The regenerated epidermis suppresses the expression of tissue morphogenesis genes accompanied by delayed hair follicle (HF) growth. Lineage tracing experiments, cell proliferation dynamics, and mathematical modeling reveal that the progeny of HF junctional zone stem cells, which undergo a morphological transformation, repair the blisters while not promoting HF development. In contrast, the contribution of interfollicular stem cell progeny to blister healing is small. These findings demonstrate that HF development can be sacrificed for the sake of epidermal wound regeneration. Our study elucidates the key cellular mechanism of wound healing in skin blistering diseases. SYNOPSIS: Subepidermal blisters (epidermal wounds) heal at the expense of hair follicle development. The progeny of hair follicle junctional zone stem cells mainly contributes to epidermal wound regeneration. The expression of tissue morphogenesis genes is downregulated in the regenerating epidermis. Hair follicle development is slowed down upon subepidermal blistering. The hair follicle junctional zone, rather than the interfollicular epidermis, is the primary keratinocyte pool for blister repair. Abstract : Subepidermal blisters (epidermal wounds) heal at the expense of hair follicle development. The progeny of hair follicle junctional zone stem cells mainly contributes to epidermal wound regeneration.